2014
DOI: 10.1155/2014/348189
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Extract ofEuchelus asperPrevents Bone Resorption in Ovariectomised Mice Model

Abstract: Marine molluscs are widely distributed throughout the world and many bioactive compounds exhibiting antiviral, antitumor, antileukemic, and antibacterial activity have been reported worldwide. The present study was designed to investigate the beneficial effect of methanol extract of Euchelus asper (EAME) on estrogen deficiency induced osteoporosis in ovariectomised mice model. Forty-two female Swiss albino mice were randomly assigned into Sham operated (Sham) group and six ovariectomised (OVX) subgroups such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…These results reveal the importance of estrogen levels in healthy men, particularly elderly men, and in male patients with cardiac diseases. In the present study, the dose of E2 used was based on previous reports (22,23). However, more studies are needed to determine the dose-response and the estrogen levels in male animals under physiological and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These results reveal the importance of estrogen levels in healthy men, particularly elderly men, and in male patients with cardiac diseases. In the present study, the dose of E2 used was based on previous reports (22,23). However, more studies are needed to determine the dose-response and the estrogen levels in male animals under physiological and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…OVX caused vaginal atrophy and this vaginal atrophy resulted from the depletion of the estrogen supplied by the ovary. Vaginal atrophy also was reflected in decreased vaginal weights (Balakrishnan et al 2014). Tibolone extensively used by Effect of placenta on menopausal symptoms postmenopausal women for the treatment of climacteric symptoms and prevention of osteoporosis has a suppressive effect on body weight (Dedeoglu et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by a thick and conoidal dull shell with brown, rosy, and black dots. Ether-soluble fractions of this organism were able to induce immunostimulated phagocytosis in vitro and immunosuppressive activity in vivo [142,143], whereas methanol extracts have been shown to exert an anti-osteoporotic effect in vivo, as indicated by the prominent anti-osteoclastogenic activity and reduction in bone loss induced by the lack of estrogen in a ovariectomised mice model [144]. Agrawal et al [145] demonstrated that methanol preparations from E. asper displayed strong anti-angiogenic potential in CAM assays due to their inhibitory role on mesodermal blood vessel migration and compartmentalization resulted, at least in part, from a decreased ECM remodelling by MMPs.…”
Section: Molluscamentioning
confidence: 99%